Identification of a gene encoding a sugar transporter as a potential target of a novel LysR‐type transcriptional regulator rluD from rhizobium required for symbiotic nodulation in soybean (Glycine max Merr.). (14th March 2019) - Chang, Huilin; Li, Jianyi; Zhu, Yongxu; Chen, Lin; Shi, Yan; Li, Shuping; Qin, Hongtao; Huang, Shiyu; Li, Qingying; Lv, Xuemeng; Tian, Sisi; Hu, Zhenbang; et al.
Abstract: Rhizobia can fine‐tune activating key genes involved in background regulation network of nodulation in effective symbiosis processes. Detecting the mechanism of the soybean‐rhizobium interaction plays a pivotal role in aiding the agricultural environment. Here, we report that LysR family transcriptional factor rluD is a novel putative gene that supports symbiosis of broad host‐range strain Sinorhizobium fredii HH103 ( S. fredii HH103) during soybean nodulation. The nodule numbers (NN) and nodule dry weight (NDW) of 'Charleston' and 'Dongnong594' (parents of recombinant inbred line [RIL] population) were reduced after inoculation with S. fredii HH103Ω rluD compared to HH103. To further elucidate the mechanism of rluD in the establishment of symbiosis, unconditional and conditional quantitative trait loci (QTLs) underlying NN and NDW were detected via a high‐generation RILs inoculated with HH103Ω rluD and wild‐type HH103. A major locus of the overlapping region between unconditional and conditional QTLs on Chromosome 6 was identified. The candidate gene Glyma.06g166800 encodes a novel sugar transporter, which might interact with rluD based on qRT‐PCR analysis. This result is valuable for elucidating the mechanism of symbiosis.